(untitled) (Alternautas, 2022)
The declared war against the tertiary education sector in Brazil comes together with severe budget cuts to the federal education system, increasing the threats to academic freedoms and episodes of violence targeting students and academic staff and a scheme to open public universities to private sector investment and management. These cuts are part of broader neoliberal policies that directly attack social rights by transforming them into commodities. In the case of Brazil, these policies not only undermine a public, high-quality and free higher education system, guaranteed by the 1988 Federal Constitution, but also public-oriented scientific research, funded by the federal government. In this article, we discuss the assaults on Brazil’s higher education system, the significant pressure on the autonomy of public universities, the limitation of funding for specific disciplines, the consequences of the current policies for the internationalisation of Brazilian universities, and the threats to local science and innovation that have caused concern for scholars and students.